APPOINTMENT OF FEMALE AS A QĀḌI (JUDGE) OF SHARI‘AH COURT OF APPEAL IN NIGERIA: A GENDER BATTLE OR RELIGIOUS STANCE - Abolaji, Abdulraheem Taofeeq (Jurnal Syariah, 2023)
The appointment of the justices is well provided for under the Nigerian constitution. However, appointment of a female as a Qāḍi of the Shari‘ah Court of Appeal in Nigeria, faith-based adjudicatory process, has remained a thing of divergence among scholars. Therefore, this article investigates whether it is permissible for a female to be appointed as a Qāḍi of the Shari‘ah Court of Appeal in Nigeria. In carrying out this research, a doctrinal method is employed which includes analysis of primary and secondary data. It then argues that the appointment or otherwise of a female as a Qāḍi should not be categorized as a gender battle, but rather a religious position, depending on the madhhab (School of Law) a given country adopts. Drawing from jurisdictions like Malaysia and Pakistan, the paper finds that a female can become a Qāḍi of the Shari‘ah Court and hold high-ranking positions in the court as there is no explicit prohibition of such appointment in the fundamental sources of Islamic Law.